Effects of Extracurricular Activities on Academic Performance of Secondary Students In Male (International Journal of Scientific Research and Management (IJSRM), 2024)
This study was conducted to determine the effects of extracurricular activities on academic performance of two selected secondary schools of Male. The study was carried out utilizing quantitative research design. The study attempted to find out whether there was any difference in academic performance between the students who spent more than five hours and less than five hours for extracurricular activities, whether there was any difference in academic performance between the students who participate and do not participate in extracurricular activities, whether there was any difference in academic performance between the students who participate in sport, pro-social activities and clubs and whether there was any difference in academic performance between female and male students who participate in extracurricular activities. This study’s sample frame comprised all ninth-grade pupils. Two hundred and sixty-nine students from grade nine of both the schools made up the study group. Each student completed a questionnaire which gathered information about their participation in extracurricular activities. Using specific criteria students who were involved and those who do not involved were found. The differences between groups were analyzed statistically using Mann Whitney U test for the first, third and last research question and Kruskul test for the second research question. Results of data analyses indicated that no significant differences were found between the students who spent more than five hours‟ for extracurricular activities and those who spent less than five hours, between the students who participate in sport, pro-social activities, and clubs and between female and male students who participate in extracurricular activities. However, there was a significant difference in academic performance between the students who participate and who do not participate in extracurricular activities.